2009
DOI: 10.1592/phco.29.9.1082
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Double‐Dose Transdermal Scopolamine

Abstract: Double-dose transdermal scopolamine may improve treatment in patients who fail to respond to a single patch by increasing the plasma scopolamine concentration, without aggravating systemic, visual, or cognitive adverse effects. Thus we recommend that a double dose can be administered safely to these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…With incremental exposure, people also can develop context specific adaptations so that, for example, they can move between a rotating artificial gravity environment and a stationary environment without either sensory motor control or motion sickness problems (Graybiel and Knepton 1978a, b; Lackner and DiZio 2000a, b, 2006). Drugs such as promethazine and scopolamine provide protective benefit (Bar et al 2009; Davis et al 1993; Graybiel and Lackner 1987; Gordon et al 2001; Klocker et al 2001; Nachum et al 2001, 2006; Simmons et al 2010). These drugs are central nervous system depressants and induce drowsiness so that they are often used in combination with dexedrine and ephedrine, respectively.…”
Section: How Can Motion Sickness Be Avoided or Attenuated?mentioning
confidence: 99%
“…With incremental exposure, people also can develop context specific adaptations so that, for example, they can move between a rotating artificial gravity environment and a stationary environment without either sensory motor control or motion sickness problems (Graybiel and Knepton 1978a, b; Lackner and DiZio 2000a, b, 2006). Drugs such as promethazine and scopolamine provide protective benefit (Bar et al 2009; Davis et al 1993; Graybiel and Lackner 1987; Gordon et al 2001; Klocker et al 2001; Nachum et al 2001, 2006; Simmons et al 2010). These drugs are central nervous system depressants and induce drowsiness so that they are often used in combination with dexedrine and ephedrine, respectively.…”
Section: How Can Motion Sickness Be Avoided or Attenuated?mentioning
confidence: 99%
“…For example, the ED50 for hippocampus-independent tone fear conditioning was about 14 times higher than the ED50 for hippocampus-dependent context conditioning, even though this comparison is made off-drug and tone and context learning occurred simultaneously. Additionally, SCOP has been used in humans to treat a variety of conditions including seasickness (46), Parkinson’s disease (47) and depression (4850). Thus, SCOP met the three characteristics we noted above, indicating it was a promising candidate for the decontextualization of extinction.…”
Section: Introductionmentioning
confidence: 99%
“…One small randomised, crossover, double blind study in healthy young men reported on double dose hyoscine patch therapy as a potential treatment for those in whom a single patch is ineffective, and concluded that two patches were safe and well tolerated in this group. 20 Faster onset of action may be obtained through administration as a nasal spray. 21 A small randomised, placebo controlled, double blind crossover trial using experimentally induced motion sickness in young adults showed the nasal preparation to be effective, with no significant decrease in alertness.…”
Section: Antimuscarinicsmentioning
confidence: 99%